Framing Operation Dudula and Anti-Immigrant Sentiment in South African Media Discourse - Tarisayi, Kudzayi Savious (Papanda Publishier, 2024)
This study investigates how the anti-immigrant group Operation Dudula is framed and constructed in South African media discourse. Utilizing framing theory and social constructionism, content analysis was conducted on media articles published after the arrest of Operation Dudula’s leader. Findings reveal Operation Dudula resonates with citizens by blaming immigrants for unemployment, although claims about foreign workers are often misleading or exaggerated. Media frames construct Operation Dudula as either tackling unemployment or engaging in xenophobic vigilantism. While perspectives on immigrants differ, dominant frames critical of Operation Dudula may constrain its activities by challenging legitimacy. However, some political support exists for Dudula’s goals. Unfortunately, vilifying immigrants obscures systemic issues that elites failed to address. Reducing xenophobic tensions requires tackling root causes of unrest, while promoting human rights and non-discrimination. This study concludes media discourse plays a role in enabling or inhibiting the activities of vigilante groups in South Africa. Nuanced understanding of anti-immigrant framing is key to addressing this complex social issue.